Is Screen Time Throughout Adolescence Related to ADHD? Findings from 1993 Pelotas (Brazil) Birth Cohort Study. Issue 3 (February 2022) - Soares, Pedro San Martin; de Oliveira, Paula Duarte; Wehrmeister, Fernando César; Menezes, Ana Maria Baptista; Gonçalves, Helen
Objective: This study investigated the association between screen time in adolescence and Attention Deficit Disorder (ADHD) at 22 years old. Method: A sample of 2333 participants aged 11 years old without ADHD from the 1993 Pelotas Birth Cohort Study (Brazil) was followed up until the age of 22. Screen time variables included time spent in television, video game and computer at 11, 15, and 18 years old. ADHD was assessed at 22 years. Results: ADHD symptoms at 22 years was positively associated with television time at 11 years, computer time at 18 years and total screen time at ages 11, 15, and 18 years. Television time at 11 years and total screen time at 18 years were associated with diagnosis of ADHD at 22 years of age. Conclusions: Our findings may contribute to future investigations of possible explanatory avenues for these associations.